Peningkatan Pelayanan Nasabah Di Baitul Maal WaTamwil (BMT): Studi Kasus di BMT Mitra Umat Islam - Parjana, Cepi (Andragogia: Journal Education Science And Islamic Studies, 2024)
This study aims to analyze the quality of customer service at Baitul Maal wa Tamwil (BMT) and identify the factors influencing customer satisfaction. Using survey and interview methods, this study collected data from customers at BMT Mitra Umat Islam The results indicate that customer satisfaction is influenced by factors such as service speed, staff friendliness, ease of access to services, and information transparency. Recommendations for improving service include staff training, technological infrastructure enhancement, and more effective communication with customers.